LIFE HISTORY STUDIES OF Montipora digitata IN PIONEER BAY, NORTH QUEENSLAND, AUSTRALIA - Esti Harpeni; Arthur Lemuel David (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Intertidal zone in reef flat is the extreme condition for many species of corals. Periodical tides, wave action and sedimentation become the main challenging factors which usually avoided by most of coral species. However, Montipora digitata is the species that found abundant in these conditions. Having relatively small and short-lived colony, forced this species to find the strategy to survive and maintain the energy efficiently. Understanding biology and life history of M. digitata in the coral reefs is the key to understanding how this species can adapt to the extreme conditions. The biology and life history of this study focused on the population size structure, reproduction, competitive interactions, investment repair and maintain and types of selection. M. digitata leaded to productivity as a strategy to cope with any extreme condition. This pattern relatively matched with r-and S-R selection.